Factors determining membership in community-based health insurance in West Africa: a scoping review - Kaba Kanko Conde; Aboubacar Mariama Camara; Manar Jallal; Mohamed Khalis; Saad Zbiri; Vincent De Brouwere (BMC, 2022)
Abstract Background In many low-income countries, households bear most of the health care costs. Community-based health insurance (CBHI) schemes have multiplied since the 1990s in West Africa. They have significantly improved their members' access to health care. However, a large proportion of users are reluctant to subscribe to a local CBHI. Identifying the major factors affecting membership will be useful for improving CBHI coverage. The objective of this research is to obtain a general overview of existing evidence on the determinants of CBHI membership in West Africa. Methods A review of studies reporting on the factors determining membership in CBHI schemes in West Africa was conducted using guidelines developed by the Joanna Briggs Institute. Several databases were searched (PubMed, ScienceDirect, Global Health database, Embase, EconLit, Cairn.info, BDPS, Cochrane database and Google Scholar) for relevant articles available by August 15, 2022, with no methodological or linguistic restrictions in electronic databases and grey literature. Results The initial literature search resulted in 1611 studies, and 10 studies were identified by other sources. After eliminating duplicates, we reviewed the titles of the remaining 1275 studies and excluded 1080 irrelevant studies based on title and 124 studies based on abstracts. Of the 71 full texts assessed for eligibility, 32 additional papers were excluded (not relevant, outside West Africa, poorly described results) and finally 39 studies were included in the synthesis. Factors that negatively affect CBHI membership include advanced age, low education, low household income, poor quality of care, lack of trust in providers and remoteness, rules considered too strict or inappropriate, low trust in administrators and inadequate information campaign. Conclusions This study shows many lessons to be learned from a variety of countries and initiatives that could make CBHI an effective tool for increasing access to quality health care in order to achieve universal health coverage. Coverage through CBHI schemes could be improved through communication, improved education and targeted financial support.